Peranan Lembaga Pemberdayaan Lembaga Perkreditan Desa (LPLPD) dalam Penyelesaian Kredit Macet - I Wayan Sastrawan, Ida Ayu Putu Widyati; Ida Ayu Putu Widyati; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
The community in Bali is greatly aided by the credit facilities with the existence of the Village Credit Institution (LPD). The institution is the lifeblood of the village’s economy. Looking through the importance of the LPD’s function, it is necessary to have a special institution having the power of empowering the LPD, so the Village Credit Institution Empowering Agency (LPLPD) is established. This study examines the role of the LPLPD in settling bad credit as well as the procedures for settling the bad credit at the LPD. This issue is examined by the normative legal research method. In empowering the LPD, the LPLPD performs its duties through technical strengthening related to administration and bookkeeping, checking, upgrading, LPD security budget management, LPD supply guarantee budget management, LPD liquidity support budget management, and control of LPD problems. LPLPD also seeks to prevent the risk of bad credit arising in the LPD through coaching that has been planned and scheduled in each district. LPLPD takes preventive or initial preventive action with technical guidance such as administrative guidance, bookkeeping including credit guidance. LPLPD does not participate in direct credit problem solving. On the other hand, these institutions provide solutions to LPD administrators to analyse the problem whether the credit process is due to the fault of the process or because the customer is not able to make payment. If the technical or the credit process that is wrong, it is the responsibility of the manager; however, if the process is correct but the customer causes a problem, the process must go through billing in accordance with the credit agreement. If there is already bad credit, the steps that must be taken are billing, restoration and if these are unhelpful then ultimately an credit guarantee auction is carried out.